The future of deterrence - Klaus-Dieter Schwarz (Stiftung Wissenschaft und Politik (SWP), 2005)
During the Cold War deterrence was centric to all strategic debates. Today, deterrence looks very much like yesterday's solution to yesterday's security problems. This study deals with the concepts and functions of deterrence in the very different conditions of the 21st century. Its purpose is to explore the possibilities and limitations of deterrence to cope with the so-called new major threats in a more complex international environment, illustrated by examples drawn from typical cases of conflicts and perpetrators of violence that shape today's international affairs, including the proliferation of weapons of mass destruction, international terrorism, and intra-states conflicts.The conclusion of the study is that deterrence in future will remain a useful instrument in the repertoire of security policies and can perfectly be used against many of the new threats in order to avoid, contain or end violent conflicts. Nuclear deterrence has largely disappeared from public perception, but continues to play a significant role in security relations between great powers and an increasingly bigger part in regional contexts. Terrorism, as well, is not immune to deterrence which aims at denial of success to this form of asymmetric warfare. By contrast, however, civil wars are among the most difficult security challenges of 21st century and cannot be solely managed with the means of deterrence. In sum, the concept of deterrence works best when used in combination with other means and methods of security and when implemented as a part of a broad strategy of exerting influence. (SWP-Research Papers / SWP)
Keywords: 320; Globale strategische Konzeption